The weakened Weibel instability of collimated fast electron beam in nanotube array. (20th January 2017) - Liao, L.; Zhao, R.; Bie, Y.; Zhang, H.; Hu, C.
Abstract: The Weibel instability of the collimated MeV fast electron beams in a nanotube array target is researched in this work. It is found that the filamentation of the fast electrons is significantly suppressed. When fast electrons propagate the nanotube array, a strong magnetic field is created near the surface of tubes to obstruct the transverse movement of the fast electrons and bend them into the inner vacuum spaces between the successive tubes. In consequence, the positive feedback loop between the magnetic field perturbation and the electrons density perturbation is broken and the Weibel instability is thus weakened. Furthermore, the calculated results by a hybrid particle-in-cell code have also proven this weakening effect on the Weibel instability. Because of the high-energy density delivered by the MeV electrons, these results indicate some significant applications in the high-energy physics, such as radiography, fast-electron beam focusing, and perhaps fast ignition.